2007
DOI: 10.1007/s12098-007-0061-7
|View full text |Cite
|
Sign up to set email alerts
|

Index for measuring child feeding practices

Abstract: It is concluded that the composite index in its present form can reflect the CF practices more holistically than just one or few behaviors studied separately. More research is needed in the direction of constituting a composite index which can then be used for research, monitoring, evaluation and much needed advocacy for complementary feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 4 publications
6
43
0
Order By: Relevance
“…No such association was calculated in the study of tea garden workers. 27 In present study in Infants >6 months of age normal nutritional status was seen in 56.90%, 27.03% and 27.27% of adequate, inadequate and no complementary feeding group respectively. Grade IV malnutrition was seen in 8.62%, 9.91% and 11.36% of adequate, inadequate and no complementary feeding group infants respectively.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…No such association was calculated in the study of tea garden workers. 27 In present study in Infants >6 months of age normal nutritional status was seen in 56.90%, 27.03% and 27.27% of adequate, inadequate and no complementary feeding group respectively. Grade IV malnutrition was seen in 8.62%, 9.91% and 11.36% of adequate, inadequate and no complementary feeding group infants respectively.…”
Section: Discussionsupporting
confidence: 45%
“…26 A study from Gujarat also showed similar result in which a significant association were revealed between positive Complementary Feeding practices and nutritional status of the Infants as measured by and Weight for Age Z score (p<0.01). 27 On reviewing literature, we could not find any study in which an association has been found between nutritional status and breast feeding upto 6 months and with complementary feeding after 6 months in comparison with undernourished Infants of Grade I, II, III, IV.…”
Section: Discussionmentioning
confidence: 85%
“…Studies in Ethiopia, Latin America and Burkina Faso reported that infant and child feeding index was a predictor of HAZ and WAZ score [13,23,24,25] (23,24,25,13). The studies done in India, Garg et al reported association between child feeding index score and under nutrition [22] whereas Srivastava et al failed to find so [26].…”
Section: Pulverized Mangifera Indica (Mango) Seed Kernel Mitigated Momentioning
confidence: 99%
“…This is because the CF practices encompass a series of inter-related behaviours that must be considered simultaneously and are, therefore, difficult to summarize into one or a few variables that accurately reflect these practices (56). …”
Section: Introductionmentioning
confidence: 99%